Предмет:
МатематикаАвтор:
анонимПрименим формулу произведения синуса и косинуса: 2sin5xcos3x - sin8x = sin2x + sin8x - sin8x = sin2x = = 2sinxcosx; Возведем выражение sinx + cosx = √0,6 в квадрат: sin^2x + 2sinxcosx + cos^2x = 0,6; 1 + 2sinxcosx = 0,6; 2sinxcosx = 1 - 0,6 = 0,4. Ответ: 0,4.
Автор:
kellentownsendДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть